Exploration of Plastic-Degrading Bacteria From Marina Beach, Semarang, Central Java - Awalina Choirunnisa Rachmawati; Anggara Mahardika; Djohan Djohan; A.B. Susanto; Bibin Bintang Andriana (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
Plastic waste has threatens the environment and affect to the economic and tourism sectors, marine life, coastal ecosystems and human health. World Wide Fund for Nature (WWF) states that 85% of waste in the oceans is plastic. The Ministry of Environment and Forestry also noted that Indonesia experienced an increase in plastic waste from 14% in 2013 to 16% in 2016.  By 2020 the volume of plastic waste in Indonesia predicted to reach 67.8 million tons. Plastic waste takes 100-500 years to completely decompose. An alternative solution is to involve microorganisms to decompose plastic polymers. However, plastic waste reducing bacteria isolated from coastal ecosystem has not been much explored. In this study, an exploration of natural bacteria that degrades plastic waste from coastal ecosystems is carried out. Plastic samples were collected from the Marina Beach Semarang, Central Java. Plastic samples were taken from a depth of 0-10 cm in three coastal ecosystems: coastal sand sediments, rocks and mangroves. Samples then isolated and screened to obtain bacteria that have the potential to degrade polyethylene. Selected bacteria were identified by biochemical physiology according to the method of Cappuccino and Sherman and classified to genus level according to Bergey's Manual of Determinative Bacteriology and Bergey's Manual of Systematic Bacteriology. The results showed that three genera of bacteria had high polyethylene degradation potential with the speed of degradation: Enterobacteriaceae 0.0091%; Moraxella spp. 0.0066%; and Pseudomonas spp. 0.0076% per week.